Progress of triazole antifungal agent posaconazole in individualized therapy. (3rd December 2022) - Shu, Yishuo; Shi, Yinping; Yang, Yilei; Dong, Zhonghua; Yi, Qiaoyan; Shi, Haiyan
Abstract: What is known and objective: Posaconazole is the second‐generation triazole antifungal agent with widespread clinical application. Posaconazole exposure is influenced by various factors such as drug interactions, disease state and diet, resulting in a high interindividual variability in many patients and failure to ensure therapeutic efficacy. Therefore, it is necessary to conduct individualized therapy on posaconazole to ensure the efficacy and safety of treatment. Methods: Articles were identified through PubMed using the keywords such as "posaconazole, " "therapeutic drug monitoring" and "Population pharmacokinetics" from 1 January 2001 to 30 April 2022. Results and discussion: In this paper, we review the individualized treatment studies of posaconazole from the three aspects of therapeutic drug monitoring, population pharmacokinetic study and Monte Carlo simulation to provide reference for in‐depth individualized posaconazole dosing studies. What is new and conclusion: This review suggests that therapeutic drug monitoring should be performed in patients taking posaconazole to adjust the dosage and assess the efficacy and cost‐effectiveness of posaconazole under different clinical conditions and different dosing regimens through Monte Carlo simulations. In the future, a more detailed delineation and comprehensive examination of posaconazole PPK for specific populations requires further study. Abstract : Posaconazole is a second‐generation triazole antifungal agent with a broad antibacterial spectrum, strong antifungal activity, high safety tolerability and cost effectiveness compared to other azole antifungal agents. The literature on posaconazole shows an increasing trend year on year. However, the pharmacokinetic process of the drug is highly individual and its blood concentration is influenced by various factors such as the drug, the patient and the food, resulting in a failure to achieve preventive or therapeutic effects. In this paper, we present a review of the individualized therapy of posaconazole from therapeutic drug monitoring, population pharmacokinetics and Monte Carlo simulation. This review will provide a reference for the rational use of posaconazole and provide theoretical support for further individualized treatment studies.